Physiological study on the flower color formation of five varieties of Lagerstroemia indica - Shuaijie LU; Ruoyong YIN; Xinru QIN; Mengjia WU; Ruchun XI; Xiaomei DENG (Huanan Nongye Daxue xuebao)
ObjectiveThis study aims to explore the color changes and influencing factors of Lagerstroemia indica flowers with different flower colors during the blooming process. MethodThe color values, contents of total chlorophyll, carotenoids, anthocyanins, total flavonoids soluble sugar, and soluble protein, as well as pH were measured at four stages for five flower colors (red, white, light pink, pink and purple). The physiological factors influencing the flower color expression of L. indica were investigated. ResultThe L* (brightness) of L. indica flowers with different colors continuously decreased during the blooming process. The a* (red-green value) and c* (saturation value) first increased and then decreased. The b* (yellow-blue value) and h (hue) exhibited varying trends. The white flowers had the highest L* and h, with the maxima of 61.61 and 1.45, respectively, while the red flowers had the highest a*, b* and c*, with the maxima of 44.83, 7.39, and 45.44 respectively. At the full blooming stage, the anthocyanin content in red flowers was the highest at 1.55 mg·g−1, whereas it remained relatively low in white and light pink flowers with 0.04 and 0.05 mg·g−1, respectively. Pink flowers displayed the highest total flavonoid content, with an average of 4.17 mg·g−1 during the blooming process. The pH of L. indica flowers of all colors were relatively high at the bud and early blooming stages, but significantly decreased at the full and late blooming stages (P < 0.05). The color values of L. indica flowers were regulated by pigment contents. Specifically, the L* exhibited a highly significant negative correlation with total chlorophyll, carotenoids, and anthocyanin contents (P < 0.01). The a* and c* showed highly significant positive correlations with these three pigments (P < 0.01). The b* showed a highly significant negative correlation with total flavonoid content (P < 0.01) and a significant positive correlation with total chlorophyll and carotenoid contents (P < 0.05). ConclusionPigment content influences petal color, pH affects flower color by influencing anthocyanin stability, and soluble sugars indirectly affect color expression. This study provides scientific evidence for understanding the physiological factors that influence the color formation of L. indica flowers.